Extracellular Vesicles Derived from Human Umbilical Cord Mesenchymal Stem Cells Promote Trophoblast Cell Proliferation and Migration by Targeting TFPI2 in Preeclampsia - Ying Chen; Chenchen Zhou; Xiaobo Zhao; Ronghua Che; Yuelin Wu; Sheng Wan; Jinda Pei; Liping Yao; Xiaolin Hua (Stem Cells International)
Preeclampsia is a pregnancy disorder characterized by systemic organ damage and high blood pressure. It has been reported that microRNA-195 (miR-195) is associated with preeclampsia. In this study, we discovered the target of miR-195 in regulating human extravillous cytotrophoblast-derived transformed cell proliferation and migration. We analyzed the clinicopathological factors of preeclampsia and normal pregnancies. The messenger ribonucleic acid (mRNA) levels of miR-195 and tissue factor pathway inhibitor 2 (TFPI2) were measured in placental tissues derived from normal and preeclampsia patients by real-time polymerase chain reaction (PCR). Human umbilical cord mesenchymal stem cell (hUC-MSC)-derived extracellular vesicles were verified by western blot. HTR8-S/Vneo cell proliferation was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, and cell migration rate was assessed by the transwell assay. Relative luciferase activities were measured in TFPI2 wild-type (WT) and mutant cells. miR-195 expression was negatively correlated with TFPI2 mRNA levels in preeclampsia patients. Extracellular vesicles derived from hUC-MSCs enhanced HTR8-S/Vneo cell proliferation and migration. In addition, miR-195 isolated from hUC-MSCs enhanced HTR8-S/Vneo cell proliferation and migration by targeting TFPI2. Our findings demonstrate that the upregulation of miR-195 in extracellular vesicles derived from hUC-MSCs promotes HTR8-S/Vneo cell proliferation and migration by targeting TFPI2.